Culinary medicine and community partnership: hands-on culinary skills training to empower medical students to provide patient-centered nutrition education. Issue 1 (1st January 2019) - Pang, Brandon; Memel, Zoe; Diamant, Carmel; Clarke, Emily; Chou, Sherene; Gregory, Harlan
ABSTRACT: Given the economic burden and numerous morbidities associated with obesity and poor dietary choices, it is increasingly important for medical students to receive education on nutrition and preventive medicine so that they are equipped to advise patients about healthy lifestyle choices. Currently, 71% of US medical schools do not reach the minimum benchmark of 25 hours of nutrition education set by the National Academy of Sciences. In order to improve the quality and quantity of nutrition education at the Keck School of Medicine of USC (KSOM), medical students and faculty have partnered with LA Kitchen (LAK), a local teaching kitchen, and the Wellness Center at LA County Medical Center (LAC+USC). They developed a hands-on preclinical culinary and nutrition course that aims to teach students practical skills and knowledge that they will be able to apply to their own lives and pass onto patients. Following the completion of the first three years of the course (2016–2018), analysis suggests that the class was well-received and has improved students' nutrition knowledge, confidence in lifestyle counseling, and personal culinary skills. Given these highly encouraging observations, the project is currently aimed at incorporating nutrition education more broadly into the required preclinical curriculum at KSOM.